2021
DOI: 10.5187/jast.2021.e57
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Paenibacillus konkukensis sp. nov. SK3146 as a potential probiotic strain

Abstract: Paenibacillus konkukensis sp. nov., SK3146 is a novel strain isolated from a pig feed. Here, we present complete genome sequence of SK3146. The genome consists of a single circular genome measuring 7,968,964 bp in size with an average guanine + cytosine (G+C) content of 53.4%. Genomic annotation revealed that the strain encodes 151 proteins related to hydrolases (EC3), which was higher than those in Bacillus subtilis and Escherichia coli . Diverse kinds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
1
Order By: Relevance
“…For monogastric animals, a P. xylanexedens strain reportedly improved broiler performance by impacting intestinal morphology, enhanced the overall immune response and reduced E. coli in the cecum [45]. Also, a P. konkukensis sp., nov. SK3146, has been proposed as a probiotic for swine [46]. For example, other Paenibacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…For monogastric animals, a P. xylanexedens strain reportedly improved broiler performance by impacting intestinal morphology, enhanced the overall immune response and reduced E. coli in the cecum [45]. Also, a P. konkukensis sp., nov. SK3146, has been proposed as a probiotic for swine [46]. For example, other Paenibacillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, probiotic feeding of P. xylanexedens , which secretes enzymes such as D-cellulose, D-fructose, D-galactose, α-D-glucose, lactose, and maltose as actively as Bacillus species, improved the BW gain and FCR in broilers under normal feeding environment [ 17 ] or challenged conditions [ 18 ]. Similarly, P. konkukensis , isolated and analyzed for complete genome sequence in our previous studies, has DNA sequences encoding various types of enzymes such as β-glucosidase, cellulase, xylanase, and protease, which can degrade various carbohydrates and anti-nutritional factors [ 23 , 24 ]. However, in this study, P. konkukensis had no measured effects on the growth parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In studies including Paenibacillus strains, P. polymyxa with antibacterial activity against pathogenic bacterial strains reduced the E. coli and Enterococcus spp. in cecal microbiota of Japanese quail [ 20 ] and decreased ileal Enterobacteriaceae counts in broilers when the strain was fed in fermented form with palm kernel cake [ 24 ]. Another study reported that P. xylanexedens ysm 1 with antibacterial activity against E. coli reduced the cecal E. coli in broilers challenged with E. coli K88 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…이들은 식품 내에서 공간 및 영양소를 차지하기 유해 미생물의 번 식을 억제하고 식품의 유해 미생물 오염을 예방할 수 있다. 또한 프로바이오틱스는 식품의 pH 값을 조절하여 식품의 산도를 유지하거나 조절하며, 발효 과정을 통해 유익한 활성 물질을 생성하여 식품 내 유해 성분을 분해하거나 억제하고, 식품의 맛, 향, 질감을 개선하기도 한다 [11][12][13][14].…”
Section: ) 프로바이오틱스의 효과unclassified